HIV-related non-Hodgkin Lymphoma. Case report and review of the literature - Giordano, Davide; Castellucci, Andrea; Merli, Francesco; Garlassi, Elisa; Pernice, Carmine (Acta Biomedica Atenei Parmensis, 2019)
Background: HIV-related Burkitt’s lymphoma with initial oropharyngeal presentation is rarely reported. The aim of this paper is to report the clinical findings of an unusual case of a patient with extranodal oropharyngeal Burkitt’s lymphoma as presenting disease of an unknown HIV positivity and acquired immunodeficiency syndrome. Methods: We reported the case of a hispanic patient with extranodal oropharyngeal Burkitt’s lymphoma as presenting disease of an unknown HIV positivity and acquired immunodeficiency syndrome. We describe the diagnostic work-up and treatment of this rare case of extranodal oropharyngeal Burkitt’s lymphoma. Results: Histological exam on oropharyngeal incision biopsy documented a Burkitt’s lymphoma. The patient underwent highly active antiretroviral therapy and chemotherapy. After two years of follow-up the patient shows no signs of recurrence from disease. Conclusions: HIV-related Burkitt’s lymphoma presenting with primary oropharyngeal involvement is rare, with rapidly progressing dysphagia, and does not respond to antibiotherapy. Patients should undergo incision biopsy to rule out a malignancy. In young adults, diagnosis of Burkitt’s lymphoma should suggest HIV infection. The importance of a prompt diagnosis in such cases is essential to correctly adequately staging the disease to start highly active antiretroviral therapy and chemotherapy as soon as possible.